1994
DOI: 10.1523/jneurosci.14-07-04433.1994
|View full text |Cite
|
Sign up to set email alerts
|

Activation of metabotropic glutamate receptors differentially affects two classes of hippocampal interneurons and potentiates excitatory synaptic transmission

Abstract: Based on responses to metabotropic glutamate receptor (mGluR) activation, we have characterized two distinct classes of interneuron in stratum (st.) oriens of the CA1 region of hippocampus. One type of interneuron was strongly excited by 1S,3R-aminocyclopentane dicarboxylic acid (ACPD), responding with a large inward current accompanied by increased baseline noise and prominent current oscillations. A second interneuron population responded with a modest inward current with no changes in baseline noise. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
276
0
1

Year Published

1996
1996
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 282 publications
(308 citation statements)
references
References 41 publications
31
276
0
1
Order By: Relevance
“…The presence of the ion current was related to the presence of the agonist; upon removal of the agonist, the ion current returned to baseline. It has previously been reported that bath perfusion of ACPD results in an oscillatory inward current with long latency (ϳ1 min) and slow time course in a subset of interneurons (McBain et al, 1994). Similar ion currents could be evoked using bath application of 100 M ACPD under the conditions used in our experiments (Fig.…”
Section: Oriens-alveus Interneurons Respond Differentially To Mglur Asupporting
confidence: 86%
See 4 more Smart Citations
“…The presence of the ion current was related to the presence of the agonist; upon removal of the agonist, the ion current returned to baseline. It has previously been reported that bath perfusion of ACPD results in an oscillatory inward current with long latency (ϳ1 min) and slow time course in a subset of interneurons (McBain et al, 1994). Similar ion currents could be evoked using bath application of 100 M ACPD under the conditions used in our experiments (Fig.…”
Section: Oriens-alveus Interneurons Respond Differentially To Mglur Asupporting
confidence: 86%
“…The ACPD-induced inward current is mediated by group I mGluRs ACPD-induced inward currents in oriens-alveus interneurons do not depend on fast synaptic transmission (McBain et al, 1994). In concordance with this finding, Figure 4 A shows that the ACPDinduced inward current is resistant to 1 M TTX.…”
Section: Oriens-alveus Interneurons Respond Differentially To Mglur Asupporting
confidence: 78%
See 3 more Smart Citations